2007
DOI: 10.1038/sj.mp.4002066
|View full text |Cite
|
Sign up to set email alerts
|

Atypical antipsychotic-induced metabolic side effects: insights from receptor-binding profiles

Abstract: Atypical antipsychotic drugs offer several notable benefits over typical antipsychotics, including greater improvement in negative symptoms, cognitive function, prevention of deterioration, and quality of life, and fewer extrapyramidal symptoms (EPS). However, concerns about EPS have been replaced by concerns about other side effects, such as weight gain, glucose dysregulation and dyslipidemia. These side effects are associated with potential long-term cardiovascular health risks, decreased medication adherenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
331
3
15

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 642 publications
(359 citation statements)
references
References 79 publications
10
331
3
15
Order By: Relevance
“…Compared with the pharmacological profile of haloperidol, the effects of clozapine are diverse and include affinity to a wide array of receptors including dopamine D4, noradrenergic a2, serotonergic 5-HT2, and cholinergic muscarinic M2 receptors (Kinon and Lieberman, 1996;Miyamoto et al, 2005;Nasrallah, 2007;Van Tol et al, 1992). As briefly mentioned in the 'Introduction', our evidence indicates that following AMPH challenges in AMPH-pretreated rats, the cortical cholinergic input system fails to respond to, and thereby to mediate, the performance of this task .…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the pharmacological profile of haloperidol, the effects of clozapine are diverse and include affinity to a wide array of receptors including dopamine D4, noradrenergic a2, serotonergic 5-HT2, and cholinergic muscarinic M2 receptors (Kinon and Lieberman, 1996;Miyamoto et al, 2005;Nasrallah, 2007;Van Tol et al, 1992). As briefly mentioned in the 'Introduction', our evidence indicates that following AMPH challenges in AMPH-pretreated rats, the cortical cholinergic input system fails to respond to, and thereby to mediate, the performance of this task .…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest D2R involvement in olanzapine activity. Although olanzapine displays slightly lower affinity for D2R than risperidone and ziprasidone [5], olanzapine has similar antagonist efficacy in D2R-mediated signaling, such as reversing dopamine D2R-mediated decreases in cAMP accumulation [32] and other signaling [33].…”
Section: Discussionmentioning
confidence: 99%
“…Antipsychotics bind to multiple neurotransmitter receptors and may work through different receptor pharmacology [5,6]. Typical antipsychotics are high-affinity dopamine D2 receptor (D2R) antagonists, which includes D2, D3, and D4 receptors, while atypical antipsychotics are antagonists of both serotonin type 2A (5-HT2A) and D2R, with additional affinities for other serotonin and dopamine receptor subtypes as well as histamine, muscarinic, and adrenergic receptors [5,7]. However, the pharmacological mechanisms to explain the particular side effects associated with these drugs are still unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, olanzapine and other atypical antipsychotic drugs such as clozapine can induce significant weight gain and further metabolic disorders including insulin resistance, diabetes and lipid metabolism dysfunction. Among antipsychotics, olanzapine has a higher risk for weight gain than the conventional antipsychotics haloperidol, chlorpromazine and fluphenazine, and its atypical counterparts risperidone, aripiprazole, sertindole, thioridazine, quetiapine, amisulpride, zotepine and ziprasidone (Allison et al, 1999, Nasrallah, 2008. Clozapine, which is also effective for use against treatment-resistant schizophrenia, may induce more weight than olanzapine (4.45kg and 4.15kg, respectively over 10-weeks) (Allison et al, 1999), however a recent study found that high dosages of olanzapine (mean dosage 34mg/day) induced significantly higher weight gain than clozapine (+5.6 ±2.0 kg olanzapine vs clozapine, mean dosage 564mg/day, after 6-months treatment) in patients with treatment-resistant schizophrenia (Meltzer et al, 2008).…”
Section: Weight Gain Side-effect Of Olanzapine and Clozapine Treatmentmentioning
confidence: 99%